INOVASI STRATEGI PEMASARAN SENTRA INDUSTRI BREM MADIUN DALAM MENGHADAPI PERSAINGAN DI MASA PANDEMI COVID-19 - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi; Kamal Ali Roziq; Aji Pamungkas; Selly Andan Ria Rossanto (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2021)
In the economy, the industrial sector has the most important role in our country. The existence of an industry can increase regional income and can create jobs. One of the industrial centers in Madiun is the industrial center for making Brem, who does not know this particular dish. Brem is processed by fermentation of cooked glutinous rice and mixed with yeast which helps to produce a tape which then takes the water to make a brem. In the village of Bwisata Kec. Wonoasri Madiun is one of the centers in making the brem, one of which is Brem Candi Mas. And we make observations there. This program aims to add insight into MSMEs in Madiun Regency, especially in the Brem Candi Mas UMKM Center, increase sales and income so that they can survive the economic crisis caused by the Covid 19 pandemic, and create new marketing strategies. This service activity is assisted by students as entrepreneurial knowledge. The innovation made is helping the digital marketing process, namely through social media such as Instagram, Facebook, and we have created a website so that the current marketing process does not only depend on manual marketing from store to store but is more effective with online marketing.